Peningkatan Pengetahuan Ibu tentang Pembuatan Bubur Tempe Sebagai Upaya Penanganan Diare pada Balita di Desa Ploso, Mojogedang, Karanganyar - Sandra Cika Febiyana; Maezaroh Afifah Saputri; Putri Lia Sari; Wahyu Widyatmoko; Winda Rosinta Sari (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Diarrhea can occur due to consumption of food or drinks contaminated by bacteria, viruses or parasites. The majority of diarrhea sufferers are children under five years old (toddlers) with a prevalence of 12.2%. Diarrhea can be fatal if diarrhea sufferers experience severe dehydration. Giving tempeh porridge to diarrhea sufferers can shorten the duration of acute diarrhea and accelerate weight gain after suffering from acute diarrhea. The results of interviews with mothers who have children under five in the Ploso area, Mojogedang, Mojogedang District, Karanganyar Regency, showed that the majority did not know about treating diarrhea in toddlers with tempeh porridge. Objective: To provide understanding to the public that tempeh porridge can treat diarrhea in toddlers. Method: applied in community service is socialization and health education regarding diarrhea and its management by providing tempe porridge. Community service activities were carried out on Tuesday 21 October 2023 at residents' homes in Ploso Mojogedang Village, Mojogedang Karanganyar District. The community service activities were attended by 11 people. Results: Observations from this health education activity showed that the majority of participants were active in asking questions and answering questions given by the community service team and were able to demonstrate again how to make tempeh porridge. Providing health education about treating diarrhea by providing tempe porridge has proven that the community's knowledge and skills increase after being given the education. Keywords: Diarrhea, Tempe Porridge, Health Education